AUTOMATED WORKSTATION FOR TRYOUT OF ESTIMATING ALGORITHMS OF POSITION OF AIRCRAFT UNDER APPROACH AND LANDING OPERATIONS - Kondrashov, Ya.; Fialkina, T.; Ryabets, O. (Science-based technologies, 2011)
For multiposition radio rangefinding navigation and landing system is justified and chosen method of mathemat-ical simulation of estimation algorithms o location of the aircraft, shown the hardware and software structure for its implementation.